Evaluation of lablab bean [Lablab purpureus (L.) sweet] genotypes: unveiling superior pod yield, nutritional quality, and collar rot resistance - Shubha, Kumari; Choudhary, Arbind Kumar; Dubey, Abhishek Kumar; Tripathi, Kuldeep; Kumar, Rakesh; Kumar, Santosh; Mukherjee, Anirban; Tamta, Manisha; Kumar, Ujjwal; Kumar, Sanjeev; Layek, Jayanta; Das, Anup (Frontiers in Nutrition, 2024)
Lablab bean [Lablab purpureus (L.) Sweet], an underutilized nutrient-dense crop holds great potential in this aspect. Despite its advantageous nutritional profile, the production, research, and consumption of lablab bean are currently limited. Addressing these limitations and unlocking the nutritional benefits of lablab beans needs to be prioritized for fighting malnutrition in local inhabitants on a global scale. Twenty five (25) genotypes of lablab bean were collected through an exploration survey in Eastern India and were evaluated in 2020-21. Among them, the nine highly diverse well-adapted genotypes were again evaluated at the experimental farm of ICAR-Research Complex for Eastern Region, Patna, Bihar, India in 2021-2022. Horticultural important traits of lablab bean were recorded by using the minimum descriptors and biochemical analysis was done by using standard protocols. Genotypic and phenotypic correlation and path coefficient analysis was done used understand relationships, interdependencies, and causal pathways between different traits. The outcome was revalidated by using principal component analysis (PCA).Results: Descriptive statistics revealed substantial heterogeneity across the traits of lablab bean evaluated.Vitamin A content showed nearly a five-fold variation, Fe ranged from 5.97-10.5mg/100g, and Vitamin C varied from 4.61-9.45 mg/100g. Earliness and dwarf growth were observed in RCPD-1 (60cm) and early flowering (41 days). RCPD-3 and RCPD-12 had high pod yield due to their high number of pods and pod weight. Pod yield was significantly correlated with the number of pods per plant (NPP) (r g = 0.995) and with average pod weight (APW) (r g = 0.882). Path coefficient analysis revealed that average pod weight had the most direct positive effect on pod yield, followed by NPP and protein content. Lablab bean genotypes showed varying responses to collar rot disease and RCPD-15 exhibiting the lowest disease intensity.Discussion: This study underscores significant diversity in lablab bean characteristics, especially in essential nutrients like vitamin A, iron, and vitamin C levels. Desirable attributes such as early flowering and dwarf growth were identified in specific genotypes. Path coefficient analysis and principal component analysis identified genotypes with superior yields and nutritional properties. These insights inform selection and breeding strategies for enhancing lablab bean production and nutritional quality.